2018
DOI: 10.3390/en11040798
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Analysis of the Inorganic Deposits from Water in Domestic and Technical Heat Exchangers

Abstract: The deposition of insoluble inorganic substances on heat exchanger surfaces has a strong negative influence on the heat transfer and thus on the performance of the apparatus and the process. The analysis of the deposits is a crucial step towards the development of suitable technologies for scaling mitigation and prevention. Such analysis, however, is challenging and often requires advanced instrumentation and sample preparation. To overcome this problem, we present a straightforward analytical approach based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…The expressive peak of Si-O highlights the presence of tobermorite (Ca 5 Si 6 O 16 (OH) 2 •H 2 O), which has been determined to be the main component of this type of cement [5,15,16]. We observed a broad band at 1430 cm −1 and sharp peaks at 874 cm −1 and 713 cm −1 (Figure 1), indicating the presence of calcium carbonates [30][31][32]. Previous results from Kiefer et al have shown a calcium carbonate spectrum with similar bands and peaks, at 1390 cm −1 , 871 cm −1 and 712 cm −1 [32].…”
Section: Physical and Chemical Properties Of The Adsorbent (Caac)mentioning
confidence: 75%
See 1 more Smart Citation
“…The expressive peak of Si-O highlights the presence of tobermorite (Ca 5 Si 6 O 16 (OH) 2 •H 2 O), which has been determined to be the main component of this type of cement [5,15,16]. We observed a broad band at 1430 cm −1 and sharp peaks at 874 cm −1 and 713 cm −1 (Figure 1), indicating the presence of calcium carbonates [30][31][32]. Previous results from Kiefer et al have shown a calcium carbonate spectrum with similar bands and peaks, at 1390 cm −1 , 871 cm −1 and 712 cm −1 [32].…”
Section: Physical and Chemical Properties Of The Adsorbent (Caac)mentioning
confidence: 75%
“…We observed a broad band at 1430 cm −1 and sharp peaks at 874 cm −1 and 713 cm −1 (Figure 1), indicating the presence of calcium carbonates [30][31][32]. Previous results from Kiefer et al have shown a calcium carbonate spectrum with similar bands and peaks, at 1390 cm −1 , 871 cm −1 and 712 cm −1 [32]. Indeed, Fang et al [30] analyzed a similar calcium silicate with the same band, at 1430 cm −1 , which according to the authors indicates the great potential of the material for releasing Ca 2+ and OH − .…”
Section: Physical and Chemical Properties Of The Adsorbent (Caac)mentioning
confidence: 86%
“…The presence of the peaks at 730-733 in the sludge confirms the presence of carbonate [52]. The strong peak around 1,100 cm -1 is attributed to sulfate [53]. These bands indicate that the sludge produced by the Al electrode mostly contains hydroxides and oxyhydroxides [2].…”
Section: Characterization Of the Sludgementioning
confidence: 77%
“…Although by EDS analysis sulfur was not found, XRF indicated its presence on both Samples 2 and 3. Upon observing the FTIR spectra it can be seen that the main peaks that present sulphate copper corrosion products are present [17,24,25,27]. They show the internal vibrational modes of sulfate ions at 1097 and 1034 cm − 1 (ν3), 879 cm − 1 (ν1), 605 cm − 1 (ν4), the signals below 500 cm − 1 are assigned to the ν2 internal mode of and to Cu-O vibrations, while the peaks at 3403 and 3319 cm − 1 are attributed to ν(OH).…”
Section: Samples 2 Andmentioning
confidence: 99%
“…The peak at 1097 cm − 1 exists, but the peaks that would represent typical sulphate copper corrosion products like brochantite, Cu 4 SO 4 (OH) 6 , antlerite, Cu 3 (SO 4 ) (OH) 4 , or posnjakite, Cu 4 SO 4 (OH)6 •H 2 0, are not present in the spectra. So, it can be assumed that the sulphate is present in an inorganic form on the sample[24,25].…”
mentioning
confidence: 99%